Analisis Tingkat Kebisingan di Lingkungan Universitas PGRI Palembang - Atina Atina; Jumingin Jumingin; Widya Rahmadani; Indah Sukria (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
The purpose of this study was to determine the level of noise caused by vehicles on campus A at PGRI Palembang University. Noise measurements were carried out in 3 different places that were passed by the vehicles of employees and students, namely the parking lot of Building A, Building B and Building C. The study was conducted in October 2020 for 5 working days of data collection. The measurement result data is analyzed by calculating the respective Leq as a measured noise level, then the Leq is compared with the quality standards recommended by the government for noise in educational institutions. The results showed that the noise in the campus A environment of PGRI Palembang University was in the range of Leq 57.3012 - 73.9548 dBA and did not meet the noise level quality standard for educational institutions, namely 55 dBA. This is because the location of the measurement is close to the traffic of vehicles.